Ozonation of erythromycin over carbon materials and ceria dispersed on carbon materials - Alexandra G. Gonçalves (2014)
Two carbon materials, multi-walled carbon nanotubes (MWCNT) and activated carbon (AC), were investigated as ozonation catalysts for the erythromycin (ERY) mineralization. In addition, in order to evaluate a possible synergetic effect between carbon materials and ceria in the ozonation of this antibiotic, two catalysts containing ceria dispersed on the surface of MWCNT and AC were prepared, characterized and tested. The results were compared with those obtained in the absence of catalyst and in the presence of ceria. The mineralization of ERY solutions was enhanced by addition of the studied catalysts. A synergetic effect between carbon materials and ceria was observed, leading to higher mineralization degrees of ERY, mainly in the presence of MWCNT containing ceria. In the catalytic ozonation with these materials both surface and bulk reactions are supposed to occur. Oxamic, oxalic and pyruvic acids were identified as final by-products during the ozonation process. Part of the original nitrogen of ERY was converted to NO3- along with small amounts of NH4- and NO2-. Microtox tests revealed that intermediates with higher acute toxicity than ERY are produced in the early stages of single and catalytic ozonation. For longer ozonation times the acute toxicity is similar whether the carbon materials are present or not, whereas it significantly decreases using carbon materials containing ceria. Successive experimental runs of ERY ozonation show that the catalysts surface suffers some limited deactivation.